Relationship of Ergonomic Risks with Muscoloskeletal Disorders (Msds) in Rubber Production Part Workers at Pt. X Jambi in 2024 - Aisyah, Fuadhatul; Rini, Willia Novita Eka; Halim, Rd. (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of this study was to determine the relationship between ergonomic risks and complaints of musculoskeletal disorders (MSDs) in rubber production workers at PT X Jambi in 2024. This study is a quantitative study using an observational design with a cross sectional approach. The population in this study were 52 people with a research sample of 47 people using total sampling as a sampling method. Based on the results of the study, the prevalence of high musculoskeletal disorder (MSDs) complaints was felt by 36 (76.6%) rubber production workers. The results of bivariate analysis showed that the variable duration of work with an unfavorable category was 21 (87.5%) with a value of (p = 0.144 > 0.05), the weight of the load with a risk category was 31 (91.2%) with a value of (p = 0.000 < 0.05), work attitude with a risk category was 31 (91.2%) with a value of (p = 0.000 < 0.05). 05), work attitude with non-ergonomic category as many as 27 (87.1%) with value (p=0.029 < 0.05), ergonomic risk level with high category as many as 28 (82.4%) with value (p=0.246 > 0.05), and work frequency with abnormal category as many as 27 (87.1%) with value (p=0.029 < 0.05).